Structure and Meaning of Sabu Traditional Architecture: A Typology-Based Descriptive Anthropological Study - Pilipus Jeraman; Reginaldo Christophori Lake; Irwan Muji Hartanto; Novenrius Kornelius Sera; Servatius Rodriques (University of Merdeka Malang, 2026)
The traditional Sabu house (ammu hawu) represents the cultural values, cosmology, and social structure of the Sabu people who inhabit the dry island environment of East Nusa Tenggara, Indonesia. This study aims to examine the structure, typology, and symbolic meanings of Sabu architecture through a descriptive–anthropological approach integrated with typological analysis. This combined approach allows the Sabu house to be understood not only as a physical entity, but also as a symbolic system that embodies ancestral relations, ecological adaptation, and socio-cultural order. Data were collected through field observations, architectural documentation (2D and 3D), interviews with customary leaders and homeowners, and triangulated with literature on vernacular architecture and ethnographic studies in Eastern Indonesia. Typological analysis was employed to identify formal patterns, the tripartite spatial structure (lower–middle–upper), the taga batu construction system, east–west orientation, and functional variations of the house as a dwelling, ritual house, and storage house. Meanwhile, anthropological analysis was used to interpret the cosmological principles, gendered spatial organization (duru–wui), dualistic symbolism, and the maritime metaphors that underpin the conceptual foundation of Sabu architecture. The findings reveal that the Sabu house constitutes a microcosmic representation of the universe, expressed through its architectural composition. Elements such as tarru duru and tarru wui, the three-tiered spatial hierarchy (roä mengarru–kelaga–damu), ritual orientation, and the sequence of house-building rituals reflect the Sabu worldview regarding life, fertility, and ancestral presence. At the settlement level, the traditional village (rae) exhibits a consistent typology marked by East–West alignment, a central sacred space (telora), and genealogically structured spatial organization. This research contributes new insights through the integrated use of typological and anthropological frameworks, the production of technical 2D–3D visual documentation, and a more comprehensive interpretation of the cosmological and symbolic dualisms that inform the spatial and structural logic of Sabu architecture. This study provides an important contribution to the broader discourse on Indonesian vernacular architecture and offers a conceptual foundation for cultural preservation as well as the development of culturally responsive design practices, particularly in the Sabu-Raijua region.